2020
DOI: 10.3390/cells9030665
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Antibody, Natural Killer Cell and Immune Mediator Profiles in Autoimmune Thyroid Diseases

Abstract: The pathogenesis of autoimmune thyroid diseases (AITD) is poorly understood and the association between different immune features and the germline variants involved in AITD are yet unclear. We previously observed systemic depletion of IgG core fucosylation and antennary α1,2 fucosylation in peripheral blood mononuclear cells in AITD, correlated with anti-thyroid peroxidase antibody (TPOAb) levels. Fucose depletion is known to potentiate strong antibody-mediated NK cell activation and enhanced target antigen-ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Both pAbs and mAbs significantly inhibited tumor formation in this model and the anti-NPTXR mAbs also enhanced the cytotoxicity of 5-FU and cisplatin in vitro, supporting the possibility that NPTXR may be a promising therapeutic target for controlling GC progression and/or for overcoming chemotherapy resistance. We also showed that the anti-cancer effects of the mAbs in vivo resulted from NPTXR antagonism rather than as mediators of ADCC [45]. Finally, we identified the precise epitope recognized by our NPTXR mAbs, which is a critical step in developing and engineering therapeutic mAbs.…”
Section: Discussionmentioning
confidence: 85%
“…Both pAbs and mAbs significantly inhibited tumor formation in this model and the anti-NPTXR mAbs also enhanced the cytotoxicity of 5-FU and cisplatin in vitro, supporting the possibility that NPTXR may be a promising therapeutic target for controlling GC progression and/or for overcoming chemotherapy resistance. We also showed that the anti-cancer effects of the mAbs in vivo resulted from NPTXR antagonism rather than as mediators of ADCC [45]. Finally, we identified the precise epitope recognized by our NPTXR mAbs, which is a critical step in developing and engineering therapeutic mAbs.…”
Section: Discussionmentioning
confidence: 85%
“…Studies have demonstrated that lncRNAs are associated specifically with autoimmune thyroid disease (AITD), including GD. Indeed, it has been proposed that rs3094228 alters the expression of thyrocyte ligands ( MICA , MICB and HLA-C) of immunoreceptors on natural killer cells in those with AITD, promoting antibody-dependent natural killer cell-mediated cytotoxicity of the thyrocyte ( 46 ), making it a potentially functional variant. Furthermore, a study by Shirasawa et al demonstrated that a polymorphism in the promoter region of a B-cell-specific antisense RNA transcript, SAS-ZFAT , is associated with susceptibility to AITD ( 44 ), and the lncRNA transcript, Heg , has demonstrated negative correlation with TRAb concentrations in untreated patients with GD ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the type of foreign antigen, the immune response can perform antiviral, antibacterial, and anti-tumor functions, depending on the synthesis of a wide range of immune cells that build the immune defense [40][41][42][43]. Factors (e.g., improper exposure to autoantigen, maladjustment of immune response and cross-antigen stimulation) may induce autoimmunity and facilitate the progress of several immune diseases [44][45][46]. Immunity can fall into innate and adaptive immunity.…”
Section: Circular Rnas In Immune Responses and Diseasesmentioning
confidence: 99%